Analisis Miskonsepsi Siswa Kelas X Pada Materi Larutan Elektrolit dan Non Elektrolit serta Reaksi Oksidasi dan Reduksi dalam Pembelajaran Kimia di SMAN 3 Kota Padang - Pinta Medina; Vivi Puspita Sari; Elmi Rahmawati (Eduscience Development Journal, 2022)
Chemistry subjects are essentially closely related to the everyday environment. Therefore, students tend to have an understanding of the concepts of Chemistry. Specific studies in Chemistry that are abstract allow students to have misconceptions, both before and after learning chemistry. Students' misconceptions influence the achievement of learning outcomes. This research is to discover misconceptions about the concept of Electrolyte and nonelectrolyte Solutions and Oxidation and Reduction Reactions in Chemistry Learning at SMAN 3 Padang City. The research subjects were students of class X 2007/2008 academic year who had studied the issue subject of electrolyte and nonelectrolyte solutions and oxidation and reduction reactions by giving diagnostic tests to students. The sampling technique used is stratified random sampling. This research was conducted in three stages. The first stage is the manufacture of diagnostic tests and has been completed. The second stage of the diagnostic test was distributed to students. The data were analyzed by descriptive statistical analysis. The third stage of the data analysis is presented with the percentage frequency. The outputs produced in this case are: (1) students who understand the concept, (2) students who experience misconceptions, (3) students who do not understand the concept.